2010
DOI: 10.1159/000320669
|View full text |Cite
|
Sign up to set email alerts
|

Massive Subcutaneus Emphysema following Endoscopic Retrograde Cholangiopancreatography with Sphincterotomy

Abstract: Although endoscopic retrograde cholangiopancreatography (ERCP) is an effective procedure for the diagnosis and treatment of the pancreatic and extrahepatic biliary tract diseases, it is still related with several complications. A female patient who underwent an ERCP with sphincterotomy developed massive subcutaneous emphysema along with pneumomediastinum and pneumoperitoneum. Although mild respiratory distress occurred, based on the absence of intaabdominal leakage of gastrografin, the patient was managed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
3
0
5
Order By: Relevance
“…Pneumothorax, pneumomediastinum and subcutaneous emphysema have also been reported in association with ERCP and sphincterotomy [2]. The constellation of pneumomediastinum with subcutaneous emphysema without pneumothorax has been described in one other case report [3], and in that report the patient was also successfully managed with conservative care. In that reported case, the 83-year-old patient had a similar presentation of subcutaneous emphysema following an ERCP and sphincterotomy for acute cholangitis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pneumothorax, pneumomediastinum and subcutaneous emphysema have also been reported in association with ERCP and sphincterotomy [2]. The constellation of pneumomediastinum with subcutaneous emphysema without pneumothorax has been described in one other case report [3], and in that report the patient was also successfully managed with conservative care. In that reported case, the 83-year-old patient had a similar presentation of subcutaneous emphysema following an ERCP and sphincterotomy for acute cholangitis.…”
Section: Discussionmentioning
confidence: 88%
“…A continuum of fascial planes connects cervical soft tissues with the mediastinum, causing subcutaneous emphysema, and rapid transfer of air across these spaces [3].…”
Section: Discussionmentioning
confidence: 99%
“…Las explicaciones que se postulan para la presencia simultánea de neumoperitoneo, neumomediastino y enfisema subcutáneo son: la perforación mucosa que permite que el aire insuflado entre en la pared y diseccione el espacio submucoso y en su progresión desgarre la misma 4 , además, la insuflación de aire presurizado para mantener la permeabi- lidad de la luz del tracto digestivo en combinación con una pequeña perforación iatrogénica no detectada durante el procedimiento, puede extenderse ampliamente a través del retroperitoneo 6 . Esto puede haber ocurrido en nuestro caso, donde es evidente que la alta presión sostenida provocó una distensión difusa de todo el tracto digestivo (Figura 1) y una lesión desgarrante -por disociación de planos de adentro/afuera a través de la pared duodenal-y cuya topografía yuxtapapilar y el edema local, facilitaron que pasara desapercibida durante el estudio; aunque no impidió visualizar la fuga de contraste durante la tomografía.…”
Section: Discussionunclassified
“…El denominado síndrome de fuga de aire 4 , cuya expresión clínica puede ser neumoperitoneo, neumoretroperitoneo, neumotórax, neumomediastino y enfisema subcutáneo, dependiendo del grado de dispersión del aire, es excepcional, siéndolo más aún su mecanismo de producción vinculado al barotrauma [3][4][5][6] y obedece la inyección de aire sostenida y/o a alta presión en el retroperitoneo, cuya extensión y evolución lesional es incierta, tanto desde el punto de vista mecánico como infeccioso. Se presenta un caso clínico cuyo interés central es el mecanismo de producción lesional que se postula, realizando análisis de los aspectos diagnósticos, terapéuticos y evolutivos, de esta excepcional situación en el contexto de la literatura sobre el tema.…”
Section: Introductionunclassified
“… 20 One case report indicated that retroperitoneal air occurred with subcutaneous emphysema following ES without symptoms. 21 These air leaks are not a cause for alarm and require no surgical intervention.…”
Section: Discussionmentioning
confidence: 99%